Aktivitas Invitro Senyawa Antimikroba Streptococcus lactis (INVITRO ACTIVITY ANTIMICROBIAL SUBSTANCE PRODUCED BY STREPTOCOCCUS LACTIS) - Suarsana, I Nyoman; Bintang, Maria; Utama, Iwan Harjono; Suartini, Ni Gusti Agung Ayu (Jurnal Veteriner; Vol 2 No 1 (2001), 2016)
Aktivitas Invitro Senyawa Antimikroba Streptococcus lactis (INVITRO ACTIVITY ANTIMICROBIAL SUBSTANCE PRODUCED BY STREPTOCOCCUS LACTIS)
Keywords: Streptococcus lactis; antimicrobial substance